Exploring the perspective of young adults about anaemia prevention; the contributions of knowledge about at-risk groups and consequences of anaemia - Audrey Benfo; Francis Zumesew; Ebenezer Bugyei Akoto; Edward Ahiakwah; Belinda Baidoo; Nana Ama Frimpomaa Agyapong; Joseph Boachie; Patrick Adu (BMC, 2023)
Abstract Background Anaemia persistently remains a grave public health challenge in most sub-Saharan African countries. Understanding the perspectives of young adults concerning the multi-factorial nature of anaemia may be an important step towards meeting the 2025 global nutrition target of halving anaemia since these individuals might be in the process of reproductive decisions. Aim To explore the relationship between students' knowledge about individuals at risk of developing anaemia, and anaemia consequences, and anaemia prevention strategies in a tertiary student cohort. Methods This sequential exploratory study adopted a mixed-methods approach to triangulate the data collection. A semi-structured questionnaire was used to gather baseline data regarding students' perspective on anaemia. Themes that emerged from the initial questionnaire data analyses guided a focus group discussion (FGD) to further explore students' perspectives on anaemia. FGD data was thematically analysed to unearth reasons behind questionnaire item selection. Structural equation modeling (SEM) was used to explore the relationship between constructs in the anaemia knowledge questionnaire. Results Overall, 543 students participated in the initial questionnaire data acquisition compared to 16 in the FGD. Our latent variable structural model showed that knowing the causes of anaemia did not significantly (p > 0.05) associate with either knowledge about anaemia consequences (b = 0.113) or knowledge about anaemia prevention strategies (b = 0.042). However, knowledge about individuals at-risk of anaemia was significantly positively associated with both anaemia prevention strategies (b = 0.306, p < 0.05) and knowledge about consequences of anaemia (b = 0.543, 95%). Moreover, knowing the consequences of anaemia seemed to significantly positively mediate the association between knowledge about at-risk groups and preventive measures that could be adopted (b = 0.410, p < 0.05). Conclusions Systems thinking public health educational campaigns that highlight the consequences of anaemia and at-risk groups are more likely to inspire the adoption of preventive strategies among young adults.